Parenting Styles of Divorced Parents and Their Influence on Their Children’s Bruxism: A Cross-Sectional Study - Moya-López M; Ruiz-Guillén A; Romero-Maroto M; Baracco B; Carrillo-Díaz M (Pediatric Health, Medicine and Therapeutics)
María Moya-López,1 Ana Ruiz-Guillén,2 Martín Romero-Maroto,2 Bruno Baracco,3 María Carrillo-Díaz2 1Doctoral Program in Health Sciences, International PhD School, Rey Juan Carlos University, Alcorcón, Spain; 2Orthodontic and Pediatric Dentistry Department in Rey Juan Carlos University, Alcorcón, Spain; 3Dental Pathology and Therapeutics Department in Rey Juan Carlos University, Alcorcón, SpainCorrespondence: Ana Ruiz-Guillén, Orthodontic and Pediatric dentistry Department in Rey Juan Carlos University, Alcorcón, Spain, Email ana.guillen@urjc.esPurpose: Parental divorce is one of the most common adverse events in childhood and can cause children emotional problems and influence their oral health. To explore differences in possible bruxism, state anxiety, coping and parenting styles between a group of divorced parents and a group of cohabiting parents.Patients and Methods: A cross-sectional study was conducted, with data collected through self-report questionnaires filled in by 186 patients (8– 16 years) and their parents. Children completed State Trait Anxiety Inventory (STAI), Self-Report Coping Measure (SRCM) and Parenting Style Scale. The Self-Reported Bruxism Questionnaire (SBQ) was completed by their parents.Results: The results showed significant differences were seen between the group of divorced parents (n=93) and the control group (n=93), with higher levels of state anxiety and possible bruxism in the group of children of divorced parents. In addition, in terms of coping strategies, externalisation and problem-solving deficits stood out. In terms of parenting style, autonomy promotion was higher. Additionally, possible bruxism was influenced by coping strategies (seeking social support), attachment-based parenting style and communication, behavioural control and state anxiety. Finally, it was found that high anxiety may act as a moderating variable in the relationship between divorced parents and possible bruxism.Conclusion: Children of divorced parents showed more possible bruxism, anxiety, coping and behavioural problems.Keywords: divorced parents, anxiety, bruxism, coping